Delayed pulmonary embolism after COVID-19 pneumonia: a case report. Issue 6 (24th November 2020) - Kanso, Mohamad; Cardi, Thomas; Marzak, Halim; Schatz, Alexandre; Faucher, Loïc; Grunebaum, Lélia; Morel, Olivier; Jesel, Laurence
Abstract: Background : Since the onset of the COVID-19 pandemic, several cardiovascular manifestations have been described. Among them, venous thromboembolism (VTE) seems to be one of the most frequent, particularly in intensive care unit patients. We report two cases of COVID-19 patients developing acute pulmonary embolism (PE) after discharge from a first hospitalization for pneumonia of moderate severity. Case summary : Two patients with positive RT-PCR test were initially hospitalized for non-severe COVID-19. Both received standard thromboprophylaxis during the index hospitalization and had no strong predisposing risk factors for VTE. Few days after discharge, they were both readmitted for worsening dyspnoea due to PE. One patient was positive for lupus anticoagulant. Discussion : Worsening respiratory status in COVID-19 patients must encourage physicians to search for PE since SARS-CoV-2 infection may act as a precipitant risk factor for VTE. Patients may thus require more aggressive and longer thromboprophylaxis after COVID-19 related hospitalization.